PELATIHAN IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS STEAM BAGI GURU RA NURUL QOLBI - Anita Puspita Julianti; Fadhilah Artanti; Dhea Ardiyanti; Riani Suci Dewanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early Childhood Education (PAUD) is an important phase in shaping children's character and basic abilities, so an innovative learning approach that is relevant to the demands of the 21st century is needed. The STEAM-based learning model (Science, Technology, Engineering, Arts, and Mathematics) is one of the effective approaches to develop critical thinking, creativity, collaboration, and communication skills. However, its implementation at RA Nurul Qolbi still faces obstacles, especially related to the limitations of teachers' understanding and skills in designing integrated learning. This study aims to describe the STEAM training process for RA teacher Nurul Qolbi, evaluate its implementation in teaching and learning activities, and identify teachers' responses to the training. Using a descriptive qualitative approach with phenomenological methods, this study involved three teachers who were purposively selected and collected data through interviews, participatory observations, and documentation, which were analyzed using Creswell's phenomenological stages. The results of the study show that STEAM training has a positive impact on improving teachers' understanding and learning practices, who begin to integrate STEAM elements in children's play activities in a contextual and creative way. Teachers' responses to training have been very positive, marked by increased awareness of the importance of real-life experiential learning. This research is expected to contribute to the development of a more applicable and reflective model for early childhood education teachers.